Synthesis of Desthiobiotin from 7,8-Diaminopel-argonic Acid in Biotin Auxotrophs of Escherichia coli K-12 - Eisenberg, Max A. (1969)
The synthesis of desthiobiotin from 7,8-diaminopelargonic acid (DAP) was demonstrated in resting cell suspensions of Escherichia coli K-12 bioA mutants under conditions in which the biotin locus was derepressed. The biosynthetically formed desthiobiotin was identified by chromatography, electrophoresis, and by its ability to support the growth of yeast and those E. coli biotin auxotrophs that are blocked earlier in the biotin pathway. Optimal conditions for desthiobiotin synthesis were determined. Desthiobiotin synthetase activity was repressed 67% when partially derepressed resting cells were incubated in the presence of 3 ng of biotin per ml. Serine, bicarbonate, and glucose stimulated desthiobiotin synthesis apparently by acting as sources of CO(2). The results of this study are consistent with an earlier postulated pathway for biotin biosynthesis in E. coli: pimelic acid → 7-oxo-8-aminopelargonic acid → DAP → desthiobiotin → biotin.